Fault-Tolerant SVPWM Control Strategy for Five-Phase PMSM under Single-Phase Open-Circuit Fault. (February 2019) - Yiguang, Chen; Zhenmao, Bao; Chenghan, Lin; Xiaobin, Zhao
Abstract: Because five-phase permanent magnet synchronous motor (PMSM) has fault-tolerant capability, it is widely used in the applications with high reliability requirements, such as electric vehicles (EVs) and hybrid vehicles. Effective fault-tolerant control strategies can promote the development of these fields. In this paper, a space vector pulse width modulation (SVPWM) control strategy for five-phase PMSM under single-phase open-circuit fault is newly proposed. This strategy adopts two methods which are based on the principles of minimum copper loss and equal amplitudes of currents to generate reference voltage vectors. Then, they are synthesized in the reconstructed fundamental α-β plane and the harmonic y -axis to reach the control goals. The efficiency of the proposed strategy is validated by simulation. And the results show that this strategy greatly improves the reliability of the five-phase PMSM drive system and meets the strict requirements of the reliability of EVs.